Diminished sensitivity of audiovisual temporal order in autism spectrum disorder - Boer, Liselotte D.; Eussen, Mart; Vroomen, Jean (Frontiers in Integrative Neuroscience, 2013)
We examined sensitivity of audiovisual temporal order in adolescents with Autism Spectrum Disorder (ASD) using an audiovisual Temporal Order Judgment (TOJ) task. In order to assess domain-specific impairments, the stimuli varied in social complexity from simple flash/beeps to videos of a handclap or a speaking face. Compared to typically-developing controls, individuals with ASD were generally less sensitive in judgments of audiovisual temporal order (larger Just Noticeable Differences, JNDs), but there was no specific impairment with social stimuli. This suggests that people with ASD suffer from a more general impairment in audiovisual temporal processing.